Alluvial Gold Mining – A Modern Day Gold Rush on the West Coast - C L. McIntosh (The Australasian Institute of Mining and Metallurgy, 2011)
The west coast of New Zealand’s south island is host to a large number of placer goldfields that stretch from the Westport area in the north to Gillespies Beach in the south and inland to the foothills of the Southern Alps. This area is host to a large number of alluvial, glacial and strand line deposits ageing in range from Recent to Tertiary. In recent years exploration models have been developed for off shore placer deposits on the continental shelf.Gold mining on the west coast has exploited placer gold resources from the 1860s to present, and with the recent surge in the gold price the industry is currently undergoing a resurgence. The current increase in mining is dominated by small-scale mechanical operations usually involving one to two people at each site; a few larger operations also exist such as the Grey River Dredge.Mining methods range from using floating bucket dredges to small diggers. Some of the mining technologies used are similar to those employed during the great gold rushes of the 19th century. Exploration and grade control techniques can be very rudimentary often relying on previous sampling programs or wide spaced bulk sample drill holes. Some bulk sample drilling is used on the larger operations as a form of grade control, most of the small operations tend not to use any ore control sampling prior to mining. Extraction techniques relying on simple gravity based designs with riffle tables or spirals are the most commonly used. Environmental standards are very high within New Zealand and require operators to return mined areas to preagreed to landforms. The high rainfall experienced on the west coast causes challenges to operators in regard to water quality. Technical issues combined with often limited capital provide for challenges to the operations.